2012
DOI: 10.1016/j.pain.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of pain and depression to self-reported sleep disturbance in patients with rheumatoid arthritis

Abstract: The objective of this paper is to assess the contribution of disease activity, pain, and psychological factors to self-reported sleep disturbance in patients with rheumatoid arthritis (RA), and to evaluate whether depression mediates the effects of pain on sleep disturbance. The sample included 106 patients with confirmed RA participated in an assessment of their disease activity, pain, psychological functioning, and sleep disturbance during a baseline evaluation prior to participating in a prospective study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 30 publications
10
82
4
2
Order By: Relevance
“…Depression in RA has been linked to an increased risk for other comorbidities and an elevated mortality 48,49 . Nicassio, et al 50,51 , has demonstrated the complex interplay of increased pain perception, sleep disturbance, helplessness, and depression in RA. Given the frequent co-occurrence of depression among patients with RA, an intervention with sustainable benefit in depressive symptoms may produce sustainable health benefits in the long term.…”
Section: Rheumatologymentioning
confidence: 99%
“…Depression in RA has been linked to an increased risk for other comorbidities and an elevated mortality 48,49 . Nicassio, et al 50,51 , has demonstrated the complex interplay of increased pain perception, sleep disturbance, helplessness, and depression in RA. Given the frequent co-occurrence of depression among patients with RA, an intervention with sustainable benefit in depressive symptoms may produce sustainable health benefits in the long term.…”
Section: Rheumatologymentioning
confidence: 99%
“…They already experienced sleeping problems and were afraid of this increasing. RA research has shown that pain and depression play a significant role in sleep disturbance [35]. However, sleeping problems might also be related to the current social situation and worries about work capacity and economic situation.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread reductions in pain pressure thresholds have been associated with moodiness and sleep disturbances [54,55], and cross-sectional surveys have found that about 8% of RA patients satisfy the FM classification criteria [56,57]. However, although these criteria may identify the subgroup of patients with the most abnormal pain processing, they may conceal the larger number of patients whose symptoms are due to similar pain mechanisms.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%